Establishing best practice for the implementation of evacuation centres for vulnerable populations: A comparative analysis of the Australian and Japanese experience. (September 2022) - Kako, Mayumi; Arbon, Paul; Ryan, Benjamin; Harada, Nahoko
Abstract: Background: Disaster evacuation centres are often the first place for disaster-affected people to stay after a disaster as a form of temporary housing. Recent major disasters in Australia and Japan have raised issues regarding access to evacuation centres by vulnerable populations. Objectives: This paper reports a comparative analysis of the Australian and Japanese experience. This study aimed to identify the challenges for stakeholders in disaster health emergency management, in relation to establishing and managing evacuation centres for vulnerable populations, as well as possible solutions to address these challenges. Methods: Semi-structured interviews were conducted with 11 participants from both countries. Interview data were analysed thematically using the NVivo software. Results: Six themes were extracted: Low awareness of the need to protect vulnerable people, ensuring adequate staffing with suitable emergency workers, responding to cultural considerations, increasing awareness of the needs of vulnerable people in communities, ensuring effective coordination within centres, and improving preparedness for cultural diversity. Conclusions: Both countries experienced similar challenges, such as a shortage of relief staff and difficulty establishing effective coordination roles. Coordination and preparedness required a clear delineation of roles and responsibilities as well as communication between local governments and stakeholders in communities during the non-disaster period.